Efektivitas Dana Insentif Daerah dalam Mendukung Pencapaian Kinerja Tertentu di Kabupaten Bengkalis - Synta Synta; Nurhazana Nurhazana (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
This study aims to determine the DID assessment criteria that were successfully obtained, the implementation of DID, the effectiveness of DID, and the impact of DID in supporting certain performance achievements in Bengkalis Regency. The type of data used in this study is qualitative data. Research data obtained from BPKAD Bengkalis Regency. The data collection techniques in this research are interviews and document studies. The results obtained are that the DID assessment criteria have not been fully achieved in Bengkalis Regency. The implementation of DID in Bengkalis Regency is carried out properly according to applicable regulations and is used in accordance with regional needs and priorities. The effectiveness of DID in Bengkalis Regency is quite effective. This can be seen from the measurement of the effectiveness of DID using the resource approach, the process approach, and the goals approach. DID has not yet given a better impact in supporting the achievement of certain performances in Bengkalis Regency.